Perubahan Struktur Perekonomian dan Pertumbuhan Ekonomi Wilayah (Economy Structural Change and Regional Economic Growth) - Bagdja Muljaridadi (Indonesian Journal of Economics and Business, 2012)
The main objective of this paper is to prove that in order to the economic growth is always accompanied by a economy structural change, and then demonstrate the role of inter-provincial trade to economic growth of indonesian provinces. Landscape analysis and LeMasne index are used as primary tools for identifying the economy structural change of the provincial level, while the panel data regression is used as a tool to measure the effect of inter-provincial trade to economic growth.Using IRIO table 2000 and 2005, the study result that over a five years turned out that there are structural change in each province with the different level. The provinces with the economic growth rate is quite advanced  such as Riau, North Sumatera, and South Sumatera  have more structural change – which is characterized by a relatively larger LeMasne Index – in contrast to provinces such as Lampung and Jambi, have small LeMasne index. For a longer period, using the IRIO table 1985-2005, regression analysis shown that one major sources of economic growth in the provinces if Indonesia are inter-regional trade – as well as physical and human capital. This study prove that endogenous growth theory can be applied for cases of regional economic growth in Indonesia.